Stress Granule Formation Induced by Measles Virus Is Protein Kinase PKR Dependent and Impaired by RNA Adenosine Deaminase ADAR1 - Okonski, Kristina M. (American Society for Microbiology, 2013)
ADAR1, an interferon (IFN)-inducible double-stranded (ds) RNA-specific adenosine deaminase, downregulates host innate responses, including activation of the dsRNA-dependent protein kinase (PKR) and induction of IFN-β mRNA. Conversely, PKR amplifies IFN-β induction by measles virus (MV) and inhibits virus protein synthesis. Formation of stress granules (SGs), cytoplasmic aggregates of stalled translation complexes and RNA-binding proteins, is a host response to virus infection mediated by translation initiation factor eIF2α phosphorylation. We examined the roles of PKR and ADAR1 in SG formation using HeLa cells stably deficient in either PKR (PKR(kd)) or ADAR1 (ADAR1(kd)) compared to control (CON(kd)) cells. Infection with either wild-type (WT) MV or an isogenic mutant lacking C protein expression (C(ko)) comparably induced formation of SG in ADAR1(kd) cells, whereas only the C(ko) mutant was an efficient inducer in control cells. Both ADAR1 and PKR colocalized with SG following infection. MV-induced; SG formation was PKR dependent but impaired by ADAR1. Complementation of ADAR1(kd) cells by expression of either p150 WT isoform or the p150 Zα (Y177A) Z-DNA-binding mutant of ADAR1 restored suppression of host responses, including SG formation and PKR activation. In contrast, neither the p110 WT isoform nor the p150 catalytic (H910A, E912A) mutant of ADAR1 complemented the ADAR1(kd) phenotype. These results further establish ADAR1 as a suppressor of host innate responses, including activation of PKR and the subsequent SG response.